Dosezi i granice simboličkog otpora. ''Proza u trapericama'' u kontekstu jugoslavenskog socijalizma - Kolanović, Maša (2014)
The main thesis of the paper implies the historically changeable characteristics of symbolical resistance in the texts of „jeans prose” (Flaker). Using jeans as a symbol of global popular culture, freedom, casualness, the American lifestyle, resistance to forms, rules, and high culture etc., jeans prose had its specific life in Yugoslav socialism which dynamically changed during the last three decades of socialist Yugoslavia. In the early sixties it was a symbolic place of critique of dominant socialist ideology and in later period, in a more commercial orientated Yugoslav society when jeans as commodity became part of everyday life, jeans prose lost its primal rebel energy and became part of the culutral mainstream.
Projekt MZOS
HRV